Rehabilitación oral completa utilizando sistema o-ring para sobredentadura inferior y prótesis total superior convencional Reporte de caso - Correa Punina, Hector Bolívar (2023)
The population of geriatric patients is rapidly increasing, as is their need for dental treatment. Dental prostheses have been a prosthetic option for patients who have lost their teeth, and this treatment helps restore functionality, aesthetics, and harmony in the oral cavity. When there are remaining teeth in the oral cavity, overdentures can be an option, which provide retention through attachments, as it has been shown in several studies that they maintain certain biological functions in the patient such as preservation of the alveolar bone, proprioception, among others. The main objective of this clinical case was to restore both masticatory function and aesthetics by using an overdenture placed on the lower premolars with an O-ring system, in combination with a conventional total prosthesis. This type of treatment can improve the patient's self-esteem by providing great psychological satisfaction. By restoring aesthetics and function, a better quality of life can be achieved.